National action plan on gender, climate change and agriculture in Senegal - Onibon Doubogan, Yvette; Segnon, Alcade C; Obossou, Esdras; Worou, Nadine; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The main objective of this report is to support the development of a national action plan on gender and climate change for Senegal. It examines gender inequalities and will assess the status, gaps and opportunities for women to advocate for gender equality in Senegal. In doing so, the action plan demonstrates the value of a gender-sensitive approach in the various sectors of the fight against climate change, and the alignment with the policies of Senegal and Africa in terms of gender and climate change